Exact Multimonopole Solutions Of The Yang-Mills-Higgs Theory. - Teh, Rosy; Khai, Ming Wong (Universiti Sains Malaysia, 2003)

(untitled)
We found some general exact static multimonopole solutions that satisfy the first order Bogomol'nyi equations and possess infinite energy. These multimonopole solutions can be categorized into two classes, namely the A2 and B2 solutions.